Examining the mediating role of digital competence and the moderating role of technostress in the effects of facilitating conditions on higher education students’ digital informal learning - Wang, Qiong; Zhao, Guoqing; Zeng, Jinglan (Australasian Journal of Educational Technology, 2024)
Although studies have highlighted the importance of facilitating conditions in enhancing students’ digital informal learning (DIL), the effect mechanism is still unclear. This study examined the mediating role of digital competence and the moderating role of technostress between facilitating conditions and DIL. Data were collected from 385 undergraduates from two Chinese universities and analysed using AMOS and SPSS. The results indicated that (a) facilitating conditions predict students’ digital competence and DIL positively; (b) digital competence has a positive mediating effect on the association between facilitating conditions and DIL; and (c) technostress plays as a negative moderator in the relationship between facilitating conditions and DIL. In conclusion, to enhance higher education students’ DIL, educators and administrators should consider facilitating conditions, digital competence and technostress. Implications for practice or policy: University administrators could facilitate students’ DIL by providing adequate infrastructure and creating a positive atmosphere for DIL. Educators should recognise the importance of students’ digital competence and create opportunities (e.g., providing sufficient elective courses and implementing reward strategies) for their development. Students could avoid experiencing too much technostress by making their DIL schedules appropriately and participating in physical activities.